Factors Influencing Consumers' Behavioral Intention to Purchase Online Tourism Products via Mobile Device - Garry, Wei-Han Tan (2019)
Traditionally purchasing tourism products were confined to either brick-or-mortar store or online, on a desktop computer. With the growing popularity of mobile devices (mdevices) and technological advancement in wireless networks, a new form of shopping channel has emerged in the tourism industry. Consumer can now purchase via mdevices. Given the benefits and potential of this channel, the acceptance however is not widespread and currently an under-addressed topic among academician. Specifically, practitioners are also skeptical if consumers are ready to accept this alternative channel. Drawing upon the Unified Theory of Acceptance and Usage of Technology (UTAUT) (i.e., Performance Expectancy, Effort Expectancy, Social Influence and Facilitating Conditions) as a baseline model, the conceptual framework was integrated with Flow Theory (i.e., Perceived Enjoyment), Psychological Characteristic (i.e., Personal Innovativeness in Information Technology and Mobile Perceived Compatibility), Social Environment (i.e., Perceived Critical Mass) and Security Concern Factors (i.e., Perceived Risk and Wireless Trust) to study on the consumers' behavioral intention to purchase. Through the use of Partial Least Squares-Structural Equation Modelling (PLS-SEM) of 503 mobile respondents collected through self-administered questionnaires, it was discovered that some of the structural paths are not consistent with past literatures. A Post Hoc Multiple Mediation Analysis has been included to discover some of the non-supported findings. Additionally, a non-parametric Permutation approach has also been conducted to discover on the gender and age differences in the decision making. The findings are mixed and therefore requires further testing. This study has valuable contributions to academicians, practitioners, and society. Academically, the integrated framework contributes to the tourism and marketing literatures by uniting UTAUT, flow theory, psychological characteristic, social environment and security concern factors in the Asian context. Practically, by focusing on the important factors affecting consumers’ decision to adopt mobile tourism shopping, organisations can create effective mobile marketing campaigns. Socially, the study contributes to job creations and revenue generation for the host country.